Effect of fragment size on growth and survival rate of soft coral Sarcophyton sp. - Dang Tran Tu, Tram; Dao , Thi Hong Ngoc; Nguyen, Thi Nguyet Hue; Ho , Son Lam; Dinh , Truong An; Doan, Van Than; Nguyen , Truong Tan Tai; Do, Hai Dang; Phan , Kim Hoang; Tran , Cong Thinh; et al. (Vietnam Journal of Marine Science and Technology, 2023)
The Sarcophyton sp., are very strong and dominant in many coral reef areas. Sarcophyton species are characterized by a distinct sterile stalk, a broad, flared, smooth, mushroomshaped top, with a wide distribution and dominance in numerous coral reef areas extending from the Red Sea and eastern Africa to the western Pacific Ocean. They are cherished in marine aquariums for their diverse colors and adaptability, but their excessive exploitation has significantly impacted resources and disrupted the balance of the soft coral biome that inhabits coral reefs. The objective of the current study was to assess the impact of fragment size (0.5 × 0.5, 1.0 × 1.0, 1.5 × 1.5, 2.0 × 2.0 and 2.5 × 2.5 cm) on survival rate, growth rate and time of attachment of coral Sarcophyton sp. in a closed seawater system. Each treatment involved three replicates with 20 cuttings per replicate and the experimental period was 90 days. The experiment showed that the size of fragment did not influence the growth rate of oral disc diameter, pedal disk diameter and the time attachment of Sarcophyton sp. However, the size of fragment effect to survival rate, growth rate of height and weight of Sarcophyton sp. colonies. These findings collectively suggest that the initial coral fragment size of 1.5 cm was suitable in laboratory conditions.